2009
DOI: 10.1002/ppap.200930105
|View full text |Cite
|
Sign up to set email alerts
|

Study of Nanoparticles Formation in a Pulsed Magnetron Discharge in Acetylene

Abstract: The aim of this work is to study in a pulsed magnetron discharge of acetylene at 10−1 Torr, the influence of tOFF parameter on roughness and morphology of films deposited on silicon substrates. By using a low power discharge (long tOFF and short tON for a given power), a coating with unique morphology is deposited. This film is formed of nanoparticles and particular agglomerates called ‘flowers’ of micrometric size. To the best of our knowledge, it's the first time that such ‘flowers’ structures have been obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 15 publications
1
20
0
1
Order By: Relevance
“…Moreover, in the material science field, nanoparticles can be used to obtain a rough surface that increases the hydrophobic properties of film. Previous work showed that plas-mas, which generate nano-or micrometer-sized particles, can lead to the formation of novel interesting surfaces called nano-or microflowers [14]. To the best of our knowledge, this is the first time that such structure was observed for plasma polymerization of acetylene.…”
mentioning
confidence: 63%
See 3 more Smart Citations
“…Moreover, in the material science field, nanoparticles can be used to obtain a rough surface that increases the hydrophobic properties of film. Previous work showed that plas-mas, which generate nano-or micrometer-sized particles, can lead to the formation of novel interesting surfaces called nano-or microflowers [14]. To the best of our knowledge, this is the first time that such structure was observed for plasma polymerization of acetylene.…”
mentioning
confidence: 63%
“…SEM pictures of some BP films (Figure 4) showed the presence of spherical structures ("nanoparticles") and unique, particular structures called "flowers" [25]. It can be seen from Table 1 that some UP or DC thin films have rough surfaces but this roughness is not caused by "nanoparticles" or "flowers" formation.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Nanostructured coatings were also deposited on Si(100) substrates in pulsed magnetron discharges using acetylene (C 2 H 2 ) as a precursor [108][109][110]. A DC power supply was modulated with different frequencies varying from 7 to 33 kHz.…”
Section: Accepted Manuscriptmentioning
confidence: 99%